Monetary evaluation of marine reserve ecosystem services in the Caribbean - Pierre Failler; Claire Montocchio; Thomas Binet; Adeline Borot de Battisti; Jean-Philippe Maréchal (National Accounting Review, 2019)
The paper presents the findings of an evaluation of the total economic value (TEV) of marine ecosystems of a planned marine reserve in “Le Prêcheur”, North of Martinique, Caribbean. Almost 95% of the TEV, estimated at EUR 58 million annually, derives from non-use values, while about 5% are from Direct use values with a predominance of leisure values, and less than 1% percent comes from the Indirect use values despite the high biodiversity interest of the location. In that regards, estimates made in the context of this study are to be considered as orders of magnitude intended to feed the strategic dialogue for the development of the future marine reserve on one hand, and budgetary decisions of public policy guidelines on the other. It is therefore essential to adopt a collaborative approach between all actors involved on the coast. Moreover, public policies must take into account the protection of marine ecosystems and even more of their enhancement in a perspective that combines economic utilitarianism and selflessness. The marine ecosystems of Le Prêcheur have indeed emerged as elements of the identity of the coastal population of Le Prêcheur but also of Martinique as a whole and, as such, must be highlighted.